Subsurface mapping of petroleum product (diesel) spillage in Apapa, Lagos, Nigeria from geophysical, lithological, and hydrogeological studies - Samson Ige Bankole; Moroof Olasunbo Oloruntola; Olateju Olatunji Bayewu; Daniel Opemipo Obasaju (Kuwait Journal of Science)
A multi-disciplinary method has been applied for the subsurface mapping of a diesel (refined petroleum product) spillage in the Apapa area of Lagos, Nigeria. The methods include geological, geophysical, hydrogeological, and geoinformatics approaches. Apapa is located within the eastern sector of the Dahomey Basin, Nigeria. Twelve profiles were probed, adopting a 2D Wenner configuration. Three 3D resistivity images were produced from the 2D profiles using ZONDRES 3D and SURFER 16. Additionally, six boreholes were drilled for lithological information and the determination of groundwater flow directions of the area. The study area is characterized by loose, fine to coarse grained sand underlain by peat. The sands were observed to be partly contaminated by diesel (spilled diesel). The 3D resistivity images revealed that the area is composed of 3 geoelectric layers; an organic debris layer (<15 Ωm), overlain by a clean sandy layer (15–54 Ωm), as well as a contaminated sand layer (>55 Ωm). The results showed that higher resistivity values were obtained at shallow depths ≤3 m which depicts the diesel contaminated sand. The 3D model also showed that the magnitude of contamination decreases from the southern part (close to the source of contamination) towards the north of the area. These results are in tandem with the principal flow direction of water which is from south to north, confirming that the pollution source is from the southern part of the area. The combination of the resistivity, groundwater flow direction, and lithological information, therefore, unraveled the source, direction, and extent of contamination in the study area for a successful remediation plan.